PENGEMBANGAN MEDIA PEMBELAJARAN MATEMATIKA BERBASIS ARTICULATE STORYLINE PADA MATERI BANGUN RUANG SISI DATAR KELAS VIII - P. A. Saputro; J. H. Lumbantoruan (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Kristen Indonesia, 2020)
This study aims to produce mathematics learning media products in the material of flat side space. The media is designed with the Articulate Storyline application with a visualization of understanding the concept of flat-sided building materials as a tool in explaining the concept of flat-sided building materials and improving student learning outcomes in class VIII of flat-side building material. The method used in this research is the Research and Development (R&D) method. This research method consists of several phases, namely: analysis of the potential and problems that exist in the research site, the second phase of literature studies and collection of information related to problem handling and based on existing potential, the third phase of designing the product, the fourth phase of designing the product, the fifth phase of expert validation, and getting tested product designs. Design validation is carried out by experts consisting of media experts, material experts, and teachers. Research data in the form of expert validation results obtained at 4.48 with the interpretation into the very valid category. In this way, the learning media is ready to be applied to the trial process and large classes in further research and development methods. Keywords:. mathematics learning media, articulate storyline, build flat side space